2007
DOI: 10.3892/or.18.5.1275
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the effects of percutaneous ethanol injection and radiofrequency ablation in cases treated with a straight or expandable electrode

Abstract: Radiofrequency ablation (RFA) has become mainstream among non-surgical treatment modalities in clinical settings for the treatment of hepatocellular carcinoma. We have previously described the novel combination therapy of percutaneous ethanol injection and RFA (PEI-RFA) and reported that this combination therapy was more effective than RFA alone in terms of the induced volume of coagulated necrosis and the energy requirement for the treatment. RFA instruments are mainly divided into two types according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A trend suggests that PEI-RFA may be utilized in 3.1–5-cm tumors. Kazutaka et al [ 38 ] reported larger areas of coagulated necrosis in the PEI-RFA group (34 ± 29.3 cm 3 ) than in the RFA group (6.5 ± 3.6 cm 3 ; P < 0.0001). The amount of ethanol injected into the tumor was significantly and positively correlated with the volume of coagulated necrosis, but not with the energy requirement.…”
Section: Discussionmentioning
confidence: 99%
“…A trend suggests that PEI-RFA may be utilized in 3.1–5-cm tumors. Kazutaka et al [ 38 ] reported larger areas of coagulated necrosis in the PEI-RFA group (34 ± 29.3 cm 3 ) than in the RFA group (6.5 ± 3.6 cm 3 ; P < 0.0001). The amount of ethanol injected into the tumor was significantly and positively correlated with the volume of coagulated necrosis, but not with the energy requirement.…”
Section: Discussionmentioning
confidence: 99%
“…LSA was associated with decreased CTA rates (OR 0.32, 95% CI 0.13-0.81) and overall survival (hazard ratio 1.47, 95% CI 1.01-2.15), as well as less comorbidities. Kazutaka and colleagues [29]. The PEI-RFA group had bigger regions of coagulated necrosis (34 29.3 cm3) than the RFA group (6.5 3.6 cm3; P 0.0001).…”
Section: [17] a Systematic Reviewmentioning
confidence: 88%